Aksesibilitas dan Ketahanan Pangan Rumah Tangga Nelayan di Pesisir Gorontalo (Studi Kasus Desa Bangga Kecamatan Paguyaman Pantai) - Maryam Dj. Koni; Yuliana Bakari; Yuriko Boeckoesoe (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
Food accessibility is a critical component in promoting household food security. Fisher families in coastal areas frequently encounter challenges securing adequate, nutritious, high-quality food, adversely affecting their food security status. This study explores the various dimensions of food accessibility and their influence on the food security of fisher households in Bangga Village, Paguyaman Pantai District, Boalemo Regency, in Gorontalo Province. During June and July 2024, the research involved 40 purposively selected respondents. The analysis focuses on three primary dimensions of food accessibility: economic, social, and physical access, while food security is treated as the dependent variable. The data analysis employs multiple linear regression alongside descriptive statistics to examine the relationships between these variables. The findings reveal that physical and economic accessibility significantly and positively affects household food security, whereas social access demonstrates a positive but statistically insignificant effect. The R² value of 0.419 indicates that the model explains 41.9% of the variation in food security among fisher households. These results underscore the urgent need for enhanced distribution infrastructure and local economic empowerment as vital strategies to improve food security. Furthermore, the study advocates for establishing coastal fisher agribusiness hubs to facilitate financial access, strengthen local markets, and support the effective marketing of fishery products.